2020
DOI: 10.1111/bjh.17061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical phenotype and haematological course of siblings with Fanconi anaemia

Abstract: Fanconi anaemia (FA) is a genetic disorder due to mutations in any of the 22 FANC genes (FANCA-FANCW) and has high phenotypic variation. Siblings may have similar clinical outcome because they share the same variants; however, such association has not been reported. We present the detailed phenotype and clinical course of 25 sibling sets with FA from two institutions. Haematological progression significantly correlated between siblings, which was confirmed in an additional 55 sibling pairs from the Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
(22 reference statements)
2
5
0
Order By: Relevance
“…All of them share height, radial and skin abnormalities, two also had microcephaly and ultrasonographic evaluations rule out renal malfomations. As expected, although these three patients share the same pathogenic FANCG genotype and a similar genetic background, their phenotypic presentation was not homogeneous, as has been evidenced in other cases [42]. Yet, they illustrate that clinical presentation in FA has a broad spectrum of severity that in this case goes from a florid presentation in FANC143 which includes five PHENOS features and uncommon findings like bifid uvula, to a more discreet presentation in patient FANC155 in whom her unilateral radial abnormality was only recorded after intentional evaluation by a dysmorphologist (Table 4).…”
Section: Discussionsupporting
confidence: 71%
“…All of them share height, radial and skin abnormalities, two also had microcephaly and ultrasonographic evaluations rule out renal malfomations. As expected, although these three patients share the same pathogenic FANCG genotype and a similar genetic background, their phenotypic presentation was not homogeneous, as has been evidenced in other cases [42]. Yet, they illustrate that clinical presentation in FA has a broad spectrum of severity that in this case goes from a florid presentation in FANC143 which includes five PHENOS features and uncommon findings like bifid uvula, to a more discreet presentation in patient FANC155 in whom her unilateral radial abnormality was only recorded after intentional evaluation by a dysmorphologist (Table 4).…”
Section: Discussionsupporting
confidence: 71%
“…As expected, although these three patients share the same pathogenic FANCG genotype and a similar genetic background, their phenotypic presentation was not homogeneous, as evidenced in other cases [40]. Yet, they illustrate that clinical presentation in FA has a broad spectrum of severity that in this case goes from a florid presentation in FANC143, which includes five PHENOS features and uncommon findings like bifid uvula, to a more discreet presentation in patient FANC155 in whom her unilateral radial abnormality was only recorded after intentional evaluation by a dysmorphologist (Table 4).…”
Section: Discussionsupporting
confidence: 62%
“…Previous reports have shown that there is not a clear correlation between specific FANCA mutations (i.e., homozygous null variants versus hypomorphic gene product) and the severity of the clinical phenotype with respect to congenital abnormalities and age at which hematologic abnormalities arise ( Castella et al 2011 ). Hematological progression significantly correlated between siblings harboring the same mutations in a recent study ( Jung et al 2020a ). However, siblings may also present with widely dissimilar phenotypes ( Faivre et al 2000 ), suggesting that other, lesser understood factors, such as environmental exposures or modifying genetic variants, may also play a role in disease manifestation.…”
Section: Introductionmentioning
confidence: 70%